Comparative studies in literature and reader formation - Guimarães, Raquel Beatriz Junqueira (Revista Letras Raras, 2024)
This article intends to discuss the possibility of Comparative Studies in Literature contributing to the formation of readers in childhood and demonstrate that the path of comparison offered by Comparative Literature inserts the reader into a process that sharpens the ability to observe, as well as fosters the ability to justify and argue. For further clarification, this debate will focus on the analysis is Ziraldo's children’s literature, O Menino Maluquinho, in three of its artistic forms: literature (book), the TV series, and the film. This analysis will demonstrate the most evident and subtle aspects of character construction, through the analysis of the conception of childhood and time brought about by the artistic pieces studied. This work is based on the concepts set forth by Tânia Carvalhal, who understands Comparative Literature as an interdisciplinary strategy, and points out how this conception brings traits of mobility to literary studies, as well as highlights the mediating nature and comparative action, which is why it is believed that reading comparatively is a virtuous path toward reader formation.